TWO-IN-ONE: CONNSHING SYNDROME OR A FORTUNATE COINCIDENCE? - Cuaño , Patricia Maria Gregoria (Journal of the ASEAN Federation of Endocrine Societies, 2023)
CASE Connshing syndrome, a rare disorder of cortisol and mineralocorticoid co-secretion by an adrenal mass, has been recognized as a distinct subgroup of primary aldosteronism. This condition is associated with increased cardiovascular risk, as well as downstream complications stemming from hypercortisolism. A 46-year-old Filipino female with long-standing hypertension and hypokalemia was diagnosed with primary aldosteronism. Low-dose and high-dose dexamethasone suppression tests also confirmed subclinical Cushing’s syndrome. Although the patient was beyond 35 years old, adrenal vein sampling was deferred due to the possible interference by hypercortisolism. Laparoscopic adrenalectomy of the left adrenal gland was done, revealing a 3.5 x 2 cm adrenal nodule. Histopathology, however, revealed two adrenal adenomas, which begs the question of whether this is a case of aldosterone and cortisol co-secretion, or if this patient was fortunate to have two separate aldosterone and cortisol-secreting adenomas localized to one gland.